Quality of life and coping strategies among caregivers of children with thalassemia major in Southern Rajasthan - Dindor, Rita; Chandel, Rajendra; Neetu; Kalasua, Deepika; Bhardwaj, Priya; Ahuja, Jyoti (International Journal of Contemporary Pediatrics, 2026)
Background: Thalassemia major (TM) is a chronic hereditary blood disorder requiring lifelong transfusions and chelation therapy, imposing a substantial physical, psychological, social, and financial burden on caregivers. Assessing caregivers’ quality of life (QoL) and coping strategies is essential to understanding their adaptive functioning and identifying areas requiring psychosocial support. To evaluate the quality of life and coping strategies among caregivers of children with thalassemia major attending a tertiary care hospital in Southern Rajasthan. Methods: A cross-sectional study among 140 caregivers of children with thalassemia major used a structured questionnaire with sociodemographic data, WHOQOL-BREF, and brief COPE. Data were analyzed using descriptive statistics, chi-square, and ANOVA, with p<0.05 as the significance level. Results: Most caregivers were male (65.7%), rural residents (80.7%), and belonged to lower socioeconomic strata (70.7%). Emotional support (85.71%), religious coping (84.29%), and informational support (82.14%) were the most frequently adopted strategies. Social relationships showed the highest QoL scores (mean 10.46±2.22), while psychological health was the most affected domain (mean 16.61±3.62). Gender and education were significantly associated with QoL across multiple domains (p<0.05), whereas duration of illness and age showed no significant association. Conclusion: Caregivers of children with thalassemia major experience considerable psychosocial strain, particularly affecting psychological and environmental well-being. Adaptive coping strategies, especially emotional and religious coping, appear to support resilience.